5 - Le mode d'accumulation mimétique et la cohérence interne du système économique national* - Krzysztof J. NERS, (Africa Development, 1985)
The idea of the world becoming more and more a «global village» is hardly questioned nowadays. Indeed, developing countries are being more and more integrated in the world economy with the major result of this integration being a disequilibrium in the relations between developped and developing countries. Various suggestions have been made as to how to solve this problem. Amongst these suggested solutions are : 1) a complete delinking from the world economy, 2) an attempt to change power rela tions between developped and developing countries, 3) a deeper integration in the world economy. It is the authors view that these solutions are not realistic at all and that what is really important to look at is the issue of the forms this integration has taken so far. To put it simply, the question to try and answer is how are developing countries participating in the inter national division of labour? For the author, the major obstacle to the industrialization process of developing countries is that these countries are trying to follow the path which developped countries have followed dis regarding the fact that development is first and foremost an experience specific to each country. Therefore the strategies and other components of a development process are there not to reach pre-fixed targets such as the one defined at Lima Conference but to direct and harness the way the national economic system operates.